Climate-Smart Agriculture Investment Prioritization Framework - International Center for Tropical Agriculture (2015)
The goal of achieving global food security is facing unprecedented challenges. Population growth and consumption patterns are increasing global food demand. This will require a 70% increase in food production by 2050, even before accounting for attempts to address undernourishment (Bruinsma 2009). Climate change is exacerbating this food security challenge by constraining future capacity to produce food globally. Given that practices of intensification and expansion have contributed to climate change (Foley et al. 2011; Tilman et al. 2011), these also need to be adapted moving forward. Advances towards sustainable development must embrace the inextricable linkages between food security, poverty, and climate change.